Knowledge, Attitude, and Practice Regarding Breast Cancer and Its Prevention Among Adolescent School-Going Girls - Bahadur Dorothy; Dube Gaurvi; Kushwaha Khushbhoo; Raikwar Pallavi; Samson Priyanka; Devi Vineeta; John Akansha; Newton Swati; Nath Aarushi (International Journal of Community Health Nursing And Practices, 2025)
Introduction: Breast cancer claims the lives of over 500,000 women globally each year. In low-resource settings, most women are diagnosed at an advanced stage of the disease, resulting in low 5-year survival rates, typically ranging between 10 and 40%. However, in regions where early detection and basic treatment are both available and accessible, the 5-year survival rate for early-stage localized breast cancer can exceed 80%. Objectives of the Study: The main goal of this study was to evaluate the knowledge, attitude, and practices (KAP) concerning breast cancer and its prevention among adolescent school girls. Additionally, the study aimed to examine the association between KAP levels and selected demographic variables. Methodology: A quantitative, non-experimental, descriptive survey design was adopted for the research. Data was collected from 50 adolescent girls attending Modern Public School in Jhansi, Uttar Pradesh, using a purposive sampling method. A structured questionnaire was employed to assess knowledge (13 items), attitude (10 items), and practices (8 items) related to breast cancer and its preventive strategies. Descriptive statistics were used for data analysis. Results: The findings revealed that 52% of participants had low knowledge levels about breast cancer, while 58% demonstrated a favorable attitude. Despite this, 86% of the girls showed inadequate practices concerning breast cancer prevention. Statistical analysis using the chi-square test showed a significant association between knowledge and age (p=0.013), attitude and age (p=0.012), and practice and grade/class (p=0.049), all at the significance level of p≤0.05. Conclusion: The study concludes that while most adolescent girls possess a favorable attitude and some level of knowledge about breast cancer, their preventive practices remain insufficient. Furthermore, there is a statistically significant relationship between knowledge, attitude, and practice and demographic factors such as age and academic grade.
Keywords: Assessment; Knowledge; attitude; breast cancer; breast self-examination (BSE); practice; preventive measures and adolescent girls